2009
DOI: 10.1063/1.3211120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of particle dipole interaction on the ac magnetically induced heating characteristics of ferrite nanoparticles for hyperthermia

Abstract: Magnetic particle dipole interaction was revealed as a crucial physical parameter to be considered in optimizing the ac magnetically induced heating characteristics of magnetic nanoparticles. The ac heating temperature of soft MFe2O4 (M=Mg,Ni) nanoparticles was remarkably increased from 17.6 to 94.7 °C (MgFe2O4) and from 13.1 to 103.1 °C (NiFe2O4) by increasing the particle dipole interaction energy at fixed ac magnetic field of 140 Oe and frequency of 110 kHz. The increase in “magnetic hysteresis loss” that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 12 publications
4
42
1
Order By: Relevance
“…A decrease in the initial susceptibility with increasing c is observed, so that the stronger the interaction between particles, the lower the hyperthermia response. Our results partially agree with those published by Wang et al 27 but run contrary to the findings in polydisperse ferrofluids reported by Jeun et al, 28 although we think that the different system analyzed in the latter ͑sample concentration is described as related to the size distribution, whereas in our case a monodisperse system is assumed͒ may be responsible for such discrepancy. Figure 4͑b͒ shows magnetization curves as a function of the amplitude of the magnetic field for c = 0.007, where the importance of the field with respect to H a is underlined: for fields H Ͻ H c = 0.48 H a there is almost no noticeable effect in the area of the cycle, whereas for values H c Ͻ H Ͻ H a large increases are observed.…”
Section: -3contrasting
confidence: 57%
“…A decrease in the initial susceptibility with increasing c is observed, so that the stronger the interaction between particles, the lower the hyperthermia response. Our results partially agree with those published by Wang et al 27 but run contrary to the findings in polydisperse ferrofluids reported by Jeun et al, 28 although we think that the different system analyzed in the latter ͑sample concentration is described as related to the size distribution, whereas in our case a monodisperse system is assumed͒ may be responsible for such discrepancy. Figure 4͑b͒ shows magnetization curves as a function of the amplitude of the magnetic field for c = 0.007, where the importance of the field with respect to H a is underlined: for fields H Ͻ H c = 0.48 H a there is almost no noticeable effect in the area of the cycle, whereas for values H c Ͻ H Ͻ H a large increases are observed.…”
Section: -3contrasting
confidence: 57%
“…However in most cases no detailed comparison between those materials are made. The exceptions are the work from Maehara et al, 42 who investigated seven types of ferrites but (unfortunately) at the micrometer range, Jeun et al 43 that reported hyperthermia studies with particles around 30 nm of three ferrites, namely Co, Ni and Mgbased ones, and within the same size range of this investigation the interesting work of Lee et al 44 which reported data on Co, Fe and Mn-based ferrites as well as exchange-coupled crystalline coreshell (hard-soft magnetic) nanostructures. Nevertheless, it is known that larger particle sizes might be influenced by incoherent rotation (curling/vortex-like for soft magnets) or domain-wall motion, which need to be correctly modeled in order to make a fair comparison with experimental data.…”
Section: Different Ferrite-based Nanoparticlesmentioning
confidence: 99%
“…Experiments range from the physical studies of the nanoparticles and the liquid 1,2 to medical studies on toxicity, 3 targeting ability, 4,5 intracellular mobility, 6 and the effectiveness of the heating. 7,8 Theoretically, most works deal with the general description of the particle assemblies, both analytically 9,10 and numerically.…”
Section: Introductionmentioning
confidence: 99%